The Archival Object: A Memoir of Disintegration - Darms, Lisa (Archivaria, 2009)
In archives, objects are often both physically and intellectually separated from textual and visual materials, even when they arrive as part of a larger manuscript or archival collection. But like other documents, objects are inscribed and can be "read" within the context of their creation. This essay uses a particular collection of objects – the artist and writer David Wojnarowicz’s Magic Box, which is part of his papers housed in the New York University Fales Library and Special Collections Downtown Collection – to examine how archival concepts such as provenance, context, description, and inscription are complicated by the presence of objects in archives. By looking at the case of an actual object collection in archives, along with both the writings of its creator and theoretical writings outside the field of archives, this essay asks how a re-examination of the role of objects in archives can contribute to our understandings of the dual symbolic and material value of all archival documents. RÉSUMÉ Dans les centres d’archives, les objets sont souvent séparés physiquement et intellectuellement des documents textuels et visuels, même quand ils font partie d’une grande acquisition de documents d’archives. Cependant, les objets, comme les autres documents, ont une valeur de témoignage et peuvent être « lus » dans leur contexte de création. Ce texte se sert d’une collection d’objets spécifique – la Magic Box [Boîte magique] de l’artiste-auteur David Wojnarowicz, qui fait partie des ses documents conservés à la New York University Fales Library and Special Collections Downtown Collection – afin d’examiner comment la présence d’objets dans des fonds d’archives complique des concepts archivistiques comme la provenance, le contexte, la description et l’enregistrement. En se servant d’un exemple concret d’une collection d’objets dans un fonds d’archives, ainsi que des textes du créateur de cette collection et des écrits théoriques provenant de l’extérieur de la discipline archivistique, ce texte explore comment un nouvel examen de la place des objets aux archives peut mener à une meilleure connaissance de la double valeur symbolique et matérielle de tout document d’archives.